Survey of leafhopper species and heir time of appearance in cotton fields at Kafer El-Sheikh - Khalafallah, E. M. (2006)
Many different species of leafhoppers were found attacking cotton plants causing serious damage to the plants. Therefore, this work was carried out to survey the species of leafhoppers and their time of appearance in cotton fields at Sakha agric. Res. Station farm, kafr el-sheikh during two successive seasons, 1999 and 2000.
Includes references.
Summary in Arabic.
1
Keywords: Cotton -- Diseases and pests -- Control; Cotton -- Egypt; Amrasca devastans; Program planning